Child and adolescent mental health care in Dutch general practice: time trend analyses - Zwaanswijk, Marieke (BioMed Central, 2011)
BACKGROUND: Because most children and adolescents visit their general practitioner (GP) regularly, general practice is a useful setting in which child and adolescent mental health problems can be identified, treated or referred to specialised care. Measures to strengthen Dutch primary mental health care have stimulated cooperation between primary and secondary mental health care and have led to an increase in the provision of social workers and primary care psychologists. These measures may have affected GPs' roles in child and adolescent mental health care. This study aims to investigate the identification and treatment of child and adolescent mental health problems in general practice over a five-year period (2004-2008). METHODS: Data of patients aged 0-18 years (N ranging from 37716 to 73432) were derived from electronic medical records of 42-82 Dutch general practices. Time trends in the prevalence of recorded mental health problems, prescriptions for psychotropic medication, and referrals to primary and secondary mental health care were analysed. RESULTS: In 2008, 6.6% of children and 7.5% of adolescents were recorded as having mental health problems; 15.2% of these children and 29.4% of these adolescents were prescribed psychotropic medication; 18.9% of these children and 22.9% of these adolescents were referred, mainly to secondary mental health care. Between 2004 and 2008, the percentages of children (chi-square: 22.06; p < 0.001) and adolescents (chi-square: 9.15; p = 0.003) who were diagnosed with mental health problems increased. An increase was also found in the percentage of children who were prescribed psychostimulants (chi-square: 8.29; p = 0.004). Prescriptions for antidepressants decreased over time in both age groups (children: chi-square: 6.80; p = 0.009; adolescents: chi-square: 13.52; p < 0.001). The percentages of children who were referred to primary (chi-square: 6.98; p = 0.008) and secondary mental health care (chi-square: 5.76; p = 0.02) increased over the years, whereas no significant increase was found for adolescents. CONCLUSIONS: Although GPs' identification of mental health problems and referrals to primary mental health care have increased, most referrals are still made to secondary care. To further strengthen primary mental health care, effective short-term interventions for child and adolescent mental health problems that can be applied in general practice need to be developed.